1977
DOI: 10.1002/ar.1091870106
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of cell turnover in the enamel organ of the rat incisor. Evidence for ameloblast death immediately after enamel matrix secretion

Abstract: During renewal of the enamel organ in the rat incisor cohorts of epithelial cells are transported sequentially through presecretory, secretory and maturation zones to the gingival margin where the life cycles of these cells terminate. This process was examined kinetically by determining the absolute flux of cells within each of these zones of amelogenesis. It was found that the efflux of ameloblasts, stratum intermedium and papillary layer cells from the presecretory zone was about equal to the efflux plus exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
2
2

Year Published

1978
1978
2008
2008

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 30 publications
6
79
2
2
Order By: Relevance
“…ln the rat incisor, continuous attrition at the incisaI end of the tooth 1& balanced by continuous production of dentin and enalDel at the apical end of the --t:ooth. More precisely, the odontogenic organ ls reaponsible, either directly or indirectly, for the production of aIl the ( hard tissues of the tooth (Smith and Warshawsky, 1977).…”
Section: L\boratory Rat Wasmentioning
confidence: 99%
“…ln the rat incisor, continuous attrition at the incisaI end of the tooth 1& balanced by continuous production of dentin and enalDel at the apical end of the --t:ooth. More precisely, the odontogenic organ ls reaponsible, either directly or indirectly, for the production of aIl the ( hard tissues of the tooth (Smith and Warshawsky, 1977).…”
Section: L\boratory Rat Wasmentioning
confidence: 99%
“…in early stages of morphogenesis (Lesot et al, 1996;Vaahtokari et al, 1996;Viriot et al, 1997;Jernvall et al, 1998;Lesot et al, 1999;Viriot et al, 2000, Matalova et al, 2004b, dentinogenesis (Bronckers et al, 1996;Vermelin et al, 1996;Franquin et al, 1998), amelogenesis (Smith and Warshawsky, 1977;Moe, 1979;Nishikawa and Sasaki, 1995;Kaneko et al, 1997) and during eruption (Schellens et al, 1982;ten Cate and Anderson, 1986). The restricted distribution patterns of apoptotic cells at these different stages suggest multiple roles for apoptosis in dental development (Peterkova et al, 2003;Matalova et al, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous cell proliferation assays in rodent incisors reconfirmed the presence of the stem cells as the source of cells for continuous growth of this type of tooth (Smith and Warshawsky, 1975, 1976, 1977Smith, 1980;Nakasone et al, 2006). Harada et al (1999) demonstrated the existence of self-renewing adult stem cells in the apical region by molecular biological Total n 2 n 2 n 2 n 2 Fig.…”
Section: Tissue Preparationmentioning
confidence: 88%